Number of Foreign Tourists and Indonesians in Bangka Belitung: A Prediction Using EMA Method - Maiti, Misratun; uddin, Syahar; Ibrahim, Malik; Perwira Negara, Habib Ratu (Journal of Sharia Economy and Islamic Tourism, 2021)
Abstract: From year to year the number of foreign tourists and tourists to Bangka Belitung has experienced ups and downs, based on data obtained from BPS obtained fluctuating charts. To find out the  number of arrivals of foreign tourists and tourists to Bangka Belitung, the time series prediction method is the Exponential Moving Average (EMA) method. In making predictions, there needs to be a pararameter used to assess how good the method is. Therefore, mad, MAPE, and MSE parameters are used. To solve the problem, of course, it is necessary to calculate the necessary components including determining the alpha value (α). So that obtained the value of α that minimizes in foreign tourists, namely α = 0.9 with MAD=769.6955, MSE=951.178.9769, and MAPE=82.4694 with the predicted result for 2020 as much as 1.3% decreased. While the value of α that minimizes in indonesian tourists is α = 0.9 with MAD = 27,946,8487, MSE = 1,198,441,984.8638, andMAPE= 18.8662 with predicted results for 2020 as much as 0.41% decreased. Abstrak: Dari tahun ke tahun jumlah pengunjung wisatawan mancanegara dan wisatawan nusantara ke Bangka Belitung mengalami pasang surut, berdasarkan data yang diperoleh dari BPS diperoleh grafik yang fluktuatif. Untuk mengetahui jumlah kedatangan wisatawan mancanegara dan wisatawan nusantara ke Bangka Belitung digunakan metode prediksi time series yakni metode Exponential Moving Average (EMA). Dalam melakukan prediksi,  perlu  adanya suatu pararameter yang digunakan untuk menilai seberapa baik metode tersebut. Oleh karena itu digunakan parameter MAD, MAPE, dan MSE. Untuk menyelesaikan permasalahan, tentunya perlu dihitung komponen-komponen yang diperlukan termasuk menentukan nilai alpha (α). Sehingga diperoleh nilai α yang meminimumkan pada wisatawan mancanegara yaitu α = 0.9 dengan MAD=769,6955, MSE=951.178,9769, dan MAPE=82,4694 dengan hasil prediksi untuk tahun 2020 sebanyak 1,3% mengalami penurunan. Sedangkan nilai α yang meminimumkan pada wisatawan nusantara yaitu α = 0.9 dengan MAD= 27.946,8487,  MSE= 1.198.441.984,8638, dan  MAPE=  18,8662dengan hasil prediksi untuk tahun 2020 sebanyak 0,41% mengalami penurunan.